2019
DOI: 10.1111/iej.13098
|View full text |Cite|
|
Sign up to set email alerts
|

2D and 3D radiographic outcome assessment of the effect of guided tissue regeneration using resorbable collagen membrane in the healing of through‐and‐through periapical lesions – a randomized controlled trial

Abstract: Aim To evaluate the effect of collagen membrane on the healing of through‐and‐through periapical lesions using 2‐dimensional (2D) and 3‐dimensional (3D) imaging techniques. Methodology Thirty‐two patients with periapical radiolucencies measuring at least 10 mm and with confirmed loss of buccal and lingual cortical plates were randomly divided into GTR and control groups. Periapical surgery was performed in both groups, using a resorbable collagen membrane in the GTR group only. 2D healing was evaluated accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(66 citation statements)
references
References 21 publications
4
38
0
Order By: Relevance
“…2017, Parmar et al . 2019) that fulfilled the inclusion criteria were included in the meta‐analysis. References listed in the eligible articles were examined, and no additional eligible studies were identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2017, Parmar et al . 2019) that fulfilled the inclusion criteria were included in the meta‐analysis. References listed in the eligible articles were examined, and no additional eligible studies were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Parmar et al . (2019) analysed the clinical and radiographic results of 30 participants with through‐and‐through periapical lesions. The results at the 12‐month follow‐up revealed that both the intervention and the control groups exhibited clear reductions in lesion sizes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large lesions take longer to heal completely or heal by scar tissue, in either condition, as long as the patient is asymptomatic the case should be followed up (Parmar et al . 2019). This was corroborated by a histopathological study of surgical retreatment re‐operations of cases assessed as non‐healed by CBCT.…”
Section: Discussionmentioning
confidence: 99%
“…For the final consideration of the study, 11 of the articles were considered for the meta-analysis. [ 8 14 15 16 17 18 19 20 21 22 23 ] Figure 1 describes the selection of the articles.…”
Section: R Esultsmentioning
confidence: 99%